Adaptive Leadership in Digital Transformation: A Comparative Case Study of Principal Management Strategies Across Contrasting Resource Contexts - Hilmi Aulia Istiqomah; Dinny Mardiana (Journal of Innovation and Research in Primary Education, 2026)
Digital transformation in education faces implementation challenges despite adequate technological infrastructure, with teachers experiencing difficulties in digital administrative tasks. This study examined how school principals enhance teachers' administrative effectiveness in the digital era through Planning, Organizing, Actuating, and Controlling (POAC) management framework across contrasting resource contexts. A comparative qualitative case study was conducted at SDN 1 Pasirwangi and SDN 1 Padaasih, Garut Regency, involving two principals, twelve teachers, and four administrative staff. Data were collected through in-depth interviews, participatory observation, and document analysis from August to September 2025, analyzed using Miles and Huberman's interactive model with source and method triangulation. Both schools achieved substantial digital administrative effectiveness through contextually adapted POAC implementation. SDN 1 Pasirwangi employed structured systems with formal ICT teams and participatory planning, optimizing government-provided infrastructure. SDN 1 Padaasih compensated for limited resources through intensive principal engagement, informal peer networks, and creative adaptation strategies. Unexpectedly, teacher age showed no correlation with digital competence development. Adaptive leadership implementation of POAC principles constitutes the critical success factor, transcending infrastructure availability. Leadership quality, particularly in fostering teacher motivation and providing solution-oriented supervision, determines digital transformation outcomes more significantly than resource abundance, challenging infrastructure-centric assumptions in educational technology literature.